2015
DOI: 10.22514/sv102.122015.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enteral nutrition on clinical outcomes among mechanically ventilated and sedated patients in the pediatric intensive care unit

Abstract: Objective. To analyze the effects of enteral nutrition on outcomes and complications of critically ill children in the pediatric intensive care unit (PICU).Design. Retrospective cohort study.Setting. PICU in a tertiary care academic medical center. Conclusions. Early adequate enteral nutrition had no statistically significant impact on the short-term clinical outcomes of PICU patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In the study of Lew et al [1] on 285 intensive care patients, no significant difference was found between patients with malnutrition and patients that do not have malnutrition in terms of dependence on mechanical ventilator. In another study conducted on 245 patients, it was shown that the duration of detachment from the mechanical ventilator was earlier and the mortality was lower in patients who started enteral nutrition early [14]. In our study, we see that both the duration of adherence to the mechanical ventilator and the stay in intensive care unit increased with low MNA-SF, high NRS 2002 and high CRP/ Albumin values.…”
Section: Discussionsupporting
confidence: 63%
“…In the study of Lew et al [1] on 285 intensive care patients, no significant difference was found between patients with malnutrition and patients that do not have malnutrition in terms of dependence on mechanical ventilator. In another study conducted on 245 patients, it was shown that the duration of detachment from the mechanical ventilator was earlier and the mortality was lower in patients who started enteral nutrition early [14]. In our study, we see that both the duration of adherence to the mechanical ventilator and the stay in intensive care unit increased with low MNA-SF, high NRS 2002 and high CRP/ Albumin values.…”
Section: Discussionsupporting
confidence: 63%
“…The association between early EN and improved outcomes has been shown in both general PICU populations and specifically in respiratory failure; however, the potential benefits in children categorized as at-risk for PARDS have not been previously demonstrated in the literature (1-9). Because of the high morbidity and mortality associated with PARDS, identifying (19,20), while others found no difference at all (21). These inconsistencies highlight the need to design prospective studies with protocolized nutrition delivery to better understand the potential benefits of this therapy in children with acute respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…Children receiving early EN in our cohort had a median PICU LOS 2 days shorter than children receiving late EN. Previous studies examining the association between LOS and timing of EN initiation in children with acute respiratory failure have suggested an inconsistent benefit of early EN, with some demonstrating a reduced PICU LOS (19, 20), while others found no difference at all (21). These inconsistencies highlight the need to design prospective studies with protocolized nutrition delivery to better understand the potential benefits of this therapy in children with acute respiratory failure.…”
Section: Discussionmentioning
confidence: 99%